Network Quality Assesment of Wireless Communication Based on Mobility Issue - D. Mahjabeen; M. A. Rashid; S. B. Mohamed (Politeknik Negeri Padang, 2018)
Up-gradation of wireless communication system is mainly based on some critical attributes like speed, coverage, interoperability, reliability, cost, security etc. This paper looks potential approaches to network quality analysis based on mobility. In this paper, focus is given to determine handover latency, vital property of mobility. This paper presents simulation to investigate handover effects-handover latency in homogeneous and heterogeneous environment using network simulator NCTUns 6.0 and simulator version 2 (NS-2) respectively for different generations of wireless communication. Also simulation is performed to find out the handover latency with respect to mobile node’s speed and then the results are compared with each other for performance analysis. The obtained results show that advanced generations of wireless communication provides low handover latency as well as higher mobility support which leads to better network performance and seamless connectivity.